2015
DOI: 10.1016/j.trim.2014.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Impaired CD8+ T cell immunity after allogeneic bone marrow transplantation leads to persistent and severe respiratory viral infection

Abstract: Rationale Bone marrow transplant (BMT) recipients experience frequent and severe respiratory viral infections (RVI). However, the immunological mechanisms predisposing to RVIs are uncertain. Therefore, we hypothesized that antiviral T cell immunity is impaired as a consequence of allogeneic BMT, independent of pharmacologic immunosuppression, and is responsible for increased susceptibility to RVI. Methods Bone marrow and splenocytes from C57BL/6(H2b) mice were transplanted into B10.BR(H2k) (Allo) or C57BL/6(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…While PGE 2 overproduction was apparently not the cause of T cell dysfunction, our data indicate that aberrant T cell function in allogeneic BMT mice is a potential explanation for delayed virus clearance. This is similar to findings in a recent study indicating that impaired clearance of Sendai virus in allogeneic BMT is due to T cell dysfunction [ 51 ]. In our study, CD8α -/- mice had higher viral loads than CD8α +/+ mice at 14 dpi, suggesting that CD8α -/- mice had a defect in clearance of virus from the lungs similar to that observed in allogeneic BMT mice.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…While PGE 2 overproduction was apparently not the cause of T cell dysfunction, our data indicate that aberrant T cell function in allogeneic BMT mice is a potential explanation for delayed virus clearance. This is similar to findings in a recent study indicating that impaired clearance of Sendai virus in allogeneic BMT is due to T cell dysfunction [ 51 ]. In our study, CD8α -/- mice had higher viral loads than CD8α +/+ mice at 14 dpi, suggesting that CD8α -/- mice had a defect in clearance of virus from the lungs similar to that observed in allogeneic BMT mice.…”
Section: Discussionsupporting
confidence: 92%
“…Because delayed virus clearance in BMT mice was not a consequence of PGE 2 overproduction, we considered other aspects of immune function that could affect MAV-1 clearance during BMT. Impaired CD8 T cell immunity contributes to increased severity of disease caused by Sendai virus in allogeneic BMT mice [ 51 ]. We therefore hypothesized that the inability of allogeneic BMT mice to efficiently clear virus from the lungs could be due to impaired T cell recruitment or function during MAV-1 infection.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was associated with decreased recruitment of both total and virus specific CD8 + T cells to the lungs in allogeneic HCT mice, and was improved by adoptive transfer of CD8 + cells from un-transplanted mice recovering from Sendai virus infection. Interestingly, syngeneic HCT mice had similar results to un-transplanted mice after infection (64). In a mouse model of adenovirus infection after allogeneic HCT, McCarthy et al showed that HCT mice had delayed viral clearance, and although pulmonary PGE 2 production was increased, the reduced production of IFN-γ and granzyme B and the delayed viral clearing noted in pulmonary CD8 + T-cells appeared independent of elevated PGE 2 production (65).…”
Section: Viral Infectionsmentioning
confidence: 97%
“…The pulmonary immune responses to these viruses after HCT are less well-described. Gowdy et al examined the effect of the respiratory viral pathogen mouse parainfluenza virus type 1 (mPIV-1), also known as Sendai virus, in both syngeneic and allogeneic HCT mice ( 64 ). Allogeneic HCT mice had increased viral load, decreased survival, and increased pulmonary inflammation after Sendai virus infection.…”
Section: Viral Infectionsmentioning
confidence: 99%